2003
DOI: 10.1034/j.1600-0889.2003.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Land-use change and management effects on carbon sequestration in soils of Russia's South Taiga zone

Abstract: The impact of land use change and management on soil C sequestration was investigated during the 1980s-1990s on gray forest soils in Pushchino, and on the soddy-podzolic soil in Prioksko-Terrasny Biosphere Reserve, Moscow Region, Russia (54 • 50 N, 37 • 35 E). Mean annual rates of C sequestration after establishment of perennials (layer 0-60 cm) were 63-182 g C m −2 and 22-43 g C m −2 for gray forest and soddy-podzolic soils, respectively. Grassing resulted in higher soil C accumulation than afforestation. Cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Root C/N ratio was increased by 24% under elevated CO 2 concentration. This result, along with the fact that timothy root biomass increased with N fertilization (Piva et al, 2013), concurs with the observation of Larionova et al (2003) that application of fertilizer increases soil C accumulation in grassland but the newly formed soil organic matter is less resistant to decomposition than that in unfertilized soil. This increase in C/N ratio was partly caused by the decrease in root N concentration that we observed at both harvests.…”
Section: Root Compositionsupporting
confidence: 89%
“…Root C/N ratio was increased by 24% under elevated CO 2 concentration. This result, along with the fact that timothy root biomass increased with N fertilization (Piva et al, 2013), concurs with the observation of Larionova et al (2003) that application of fertilizer increases soil C accumulation in grassland but the newly formed soil organic matter is less resistant to decomposition than that in unfertilized soil. This increase in C/N ratio was partly caused by the decrease in root N concentration that we observed at both harvests.…”
Section: Root Compositionsupporting
confidence: 89%
“…The first was the abandonment of agricultural land. Estimates of the total area of arable lands withdrawn form agricultural use given for the period 1990-2005 diverge widely ranging from 10.1 (FAOSTAT) to 34.0 Mha (Larionova et al, 2003) Kharuk et al, 2010). In the next section we also provide a separate assessment of these effects based on model results and experimental evidence.…”
Section: Land Use Change In Leamentioning
confidence: 99%
“…Where farming ceases, significant amounts of carbon can be sequestered as succession replaces farmland with grasslands, shrublands, and finally forests (Houghton, 1999;Post & Kwon, 2000;Rhemtulla et al, 2009). Yet, despite widespread postsocialist farmland abandonment in Eastern Europe and the former Soviet Union, resulting carbon fluxes have so far only been assessed in two studies (Larionova et al, 2003;Vuichard et al, 2008). Focusing on soil carbon, a process-driven ecosystem model revealed that cropland-grassland conversions in European Russia resulted in a net carbon sink of up to 64 Tg C between 1991 and 2000 (Vuichard et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on soil carbon, a process-driven ecosystem model revealed that cropland-grassland conversions in European Russia resulted in a net carbon sink of up to 64 Tg C between 1991 and 2000 (Vuichard et al, 2008). Similarly, downscaling carbon sequestration rates measured in abandoned fields around Moscow suggest cropland abandonment may offset a significant amount of Russia's industrial CO 2 emissions (Larionova et al, 2003). Both prior studies focused solely on cropland-grassland conversions although carbon storage potential in regrowing forests may be much higher (Houghton, 2005;Luyssaert et al, 2008).…”
Section: Introductionmentioning
confidence: 99%